Technological Progress, Occupational Structure and Gender Gaps in the German Labour Market - Ronald Bachmann; Myrielle Gonschor (Institute of Labor Economics (IZA), 2022)
We analyze if technological progress and the corresponding change in the occupational structure have improved the relative position of women in the labour market. We show that the share of women rises most strongly in non-routine cognitive and manual occupations, but declines in routine occupations. While the share of women also rises relatively strongly in high-paying occupations, womens' individual-level wages lag behind which implies within-occupation gender wage gaps. A decomposition exercise shows that composition effects with respect to both individual and job characteristics can explain the rise of female shares in the top tier of the labour market to an extent. However, the unexplained part of the decomposition is sizeable, indicating that developments such as technological progress are relevant.
Keywords: J21; J31; O33; 330; female labour market participation; occupations; tasks; technological progress